The Impact of Lifestyle on Hypertension in Adolescents: Literature Review - Putri, Fonny Kurnia; Tarigan, Renny Adelia; Roza, Nelli; Handayani, Trisna Yuni (Nusantara Science and Technology Proceedings, 2024)
Hypertension is a non-communicable disease that increases the risk of heart, brain, kidney, and other diseases. This disease can occur at any age, including adolescents and risk factors for hypertension in adolescence include BMI, insufficient sleep duration, low physical activity, poor diet, alcohol consumption, and smoking behavior. The purpose of this study was to determine lifestyle factors that influence the incidence of hypertension in adolescents. This research method is a literature review that aims to find the influence of lifestyle on the incidence of hypertension in adolescents. This research uses the PRISMA method, which is considered appropriate to achieve the research objectives. The PRISMA method consists of five steps: determining the research topic, searching for relevant sources, selecting relevant sources, classifying and analyzing these sources, and compiling a summary of research results (Ginting & Hadi, 2023). To start, use PubMed, Google Scholar, and SciSpace as research databases. The literature search used keywords in Indonesian and English, such as "lifestyle", "hypertension", "adolescence", "lifestyle" and "hypertension in adolescent". PubMed found 10,699 articles, Google Scholar found 6,940 articles, and databases SciSpace found 60 articles. The results of this literature review showed that lifestyle factors affecting the incidence of hypertension in adolescents are BMI, physical activity, smoking behavior, alcohol consumption, sleep duration, and poor diet (fat intake). In this study, lifestyles that influence the incidence of hypertension in adolescents are physical activity, smoking behavior, alcohol consumption, sleep duration, and poor diet (fat intake).